Comparison of cognitive ability and its distribution between men with autism spectrum disorder and attention-deficit/hyperactivity disorder - Hirokazu Doi; Yoshifumi Nakamura; Ayaka Nakai; Chieko Kanai; Haruhisa Ohta (PLoS ONE, 2026)
Objectives Clarification of the strengths and weaknesses of cognitive ability is essential to our understanding of the characteristics of autism spectrum disorder and attention deficit/hyperactivity disorder. However, whether individuals with these conditions exhibit distinct patterns of cognitive ability remains unclear. To address this point, we aimed to compare the cognitive profiles of patients with autism spectrum disorder with those of patients with attention deficit/hyperactivity disorder by placing special emphasis on the distribution of cognitive function within each group. Methods This study compared the Wechsler Adult Intelligence Scale index scores of men with autism spectrum disorder and attention deficit/hyperactivity disorder. A machine learning model was trained to classify autism spectrum disorder and attention deficit/hyperactivity disorder based on the subtest scores. The conformity of the within-group distribution of each index score to a normal distribution was also tested. Results Individuals with autism spectrum disorder scored higher than those with attention deficit/hyperactivity disorder in the Verbal Comprehension Index and Working Memory Index, while the opposite pattern was observed for the Perceptual Organization Index. The classification performance of the machine learning model was above chance level. The distributions of the Verbal Comprehension Index and Perceptual Organization Index deviated significantly from a normal distribution only in the autism spectrum disorder group. The results of Gaussian mixture clustering indicated that men with autism spectrum disorder could be divided into two distinct clusters based on their Verbal Comprehension Index scores. Conclusions Our findings indicate that men with autism spectrum disorder and attention deficit/hyperactivity disorder show distinct cognitive profile patterns from each other. The distribution of some of the index scores deviated from the normal distribution only in autism spectrum disorder, which supports the view that autism spectrum disorder comprises heterogeneous subgroups with different cognitive profiles.